2020
DOI: 10.1007/s00228-020-02960-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drug-drug interaction of lusutrombopag, a thrombopoietin receptor agonist, via metabolic enzymes and transporters

Abstract: Purpose Drug-drug interaction (DDI) potentials of lusutrombopag, a thrombopoietin receptor agonist, on the activity of cytochrome P450 (CYP) 3A and of cyclosporine, which inhibits P-glycoprotein and breast cancer resistance protein, on lusutrombopag pharmacokinetics were assessed via clinical studies and physiologically based pharmacokinetic (PBPK) modeling. Methods The effect of lusutrombopag on midazolam (a CYP3A probe substrate) pharmacokinetics was assessed in 15 healthy subjects receiving a single midazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…When the contribution ratio to lusutrombopag metabolism for CYP4 is 37%, CYP4 inhibitor increases the AUC of lusutrombopag at most 1.6-fold (Rodrigues 2008). The clinical DDI study with cyclosporine, a CYP3A4 inhibitor, indicated the fold increase of lusutrombopag AUC was 1.19 (Katsube et al 2020), suggesting the contribution of CYP3A4 for this drug metabolism is low. Considering that lusutrombopag was found to be metabolized primarily by CYP4A with minor contributions of CYP3A4 in this study, it could be concluded that the pharmacokinetics of lusutrombopag would be minimally or modestly changed via inhibition or induction for metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…When the contribution ratio to lusutrombopag metabolism for CYP4 is 37%, CYP4 inhibitor increases the AUC of lusutrombopag at most 1.6-fold (Rodrigues 2008). The clinical DDI study with cyclosporine, a CYP3A4 inhibitor, indicated the fold increase of lusutrombopag AUC was 1.19 (Katsube et al 2020), suggesting the contribution of CYP3A4 for this drug metabolism is low. Considering that lusutrombopag was found to be metabolized primarily by CYP4A with minor contributions of CYP3A4 in this study, it could be concluded that the pharmacokinetics of lusutrombopag would be minimally or modestly changed via inhibition or induction for metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies L-PLUS 1 and PLUS 2 were two randomized, double-blind, phase 3 trials; they demonstrated that lusutrombopag could effectively raise PLT and lower the requirements for platelet transfusion [12,13]. Moreover, there is an absence of restrictions on food and clinically significant interactions between drugs [14,15]. Unfortunately, there is no evidence-based data for lusutrombopag in a Chinese cohort yet.…”
Section: Introductionmentioning
confidence: 99%